(untitled) (Experimental biology, 2016)
We analyzed the circadian rhythms of some characteristics of the ECG (heart rate and the number of completed QRS) of students of an university during examinations. Paired t-test daily dynamics of average heart rate and QRS data during examinations and control, regardless of the season showed a significant increase of MESOR (p = 0.019) and a shift of acrophase during exams (p = 0.008). Spectrum of heart rate of students showed high statistical significance for 24-hour rhythm in control (p